Opaque Technologies - Parra Cancino, Juan; "(Virtual) Presence!? Musical performances in hybrid spaces" Freie Universität Berlin (2024)
solo electronics and networked ensemble
Lecture and networked performance
FRIS
Editorial review
Keywords: Music, Thought and Technology